Pengaruh Kepribadian Siswa Dan Metode Mengajar Guru Terhadap Hasil Belajar Tematik Pada Siswa Sekolah Dasar - Aulia, Tazkya; Wandini, Rora Rizki; Mawaddah, Tantri (Jurnal Ilmiah Wahana Pendidikan, 2023)
Student thematic learning outcomes refer to the achievements or learning achievements achieved by students within the thematic learning framework. Thematic learning is a learning approach that integrates various subjects into one particular theme or topic. The factors are divided into two, namely internal factors and external factors. This research method is quantitative with a descriptive approach, the population in this study is PGMI students who are already PPL in elementary school and the sample is 10 respondents. The data collection method is in the form of a questionnaire. The purpose of this research is to find out whether Student Personality and Teacher Teaching Methods affect Thematic Learning Outcomes in elementary school students.